Interview with Gregory G. Maskarinec - Subedi, Madhusudan; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Professor Gregory G. Maskarinec (May 16, 1951-June 16, 2022) was a member of the International Advisory Board of the Dhaulagiri Journal of Sociology and Anthropology and Professor and Director at the Office of Global Health and International Medicine, Departments of Native Hawaiian Health and Family Medicine and Community Health John A. Burns School of Medicine, University of Hawai'i. He came to Nepal, in 1977, as a Peace Corps Volunteer and served as a mathematics teacher in a school in the Jajarkot District. He explored Nepali society and culture and received his MA and PhD in shamanism. He has published several books and papers on shamanism, including "The Rulings of the Night: An Ethnography of Nepalese Shaman Oral Texts". In 1981, he won Tribhuvan University's Mahendra Scholarship and received a highly prestigious prize (the Birendra Pranyalankar) from the late King Birendra Bir Bikram Shah Dev. In addition to his significant contributions to Medical Anthropology, Prof. Gregory was a nature-lover, peaceful, devoted to generating and sharing knowledge, and supportive. He had good relationships with high-level scholars, literature artists, and politicians of Nepal. He also participated in literature festivals in rural areas and promoted local arts and artists. He had visited more than 70 districts of Nepal. Prof. Gregory suffered from cancer and had several operations done. In August 2020, he passed away from COVID-19. We are grateful to him for allowing us to publish his interview in our Journal. The interview captured his ideas, thoughts, understanding of anthropology, works in Nepal, and personal life. For the sustainability of the Dhaulagiri Journal of Sociology and Anthropology, at the end of his life, he donated US$ 5000. The journal family is always grateful for his invaluable contribution